Pragmatism, law, and literature - Kenny, David, 1986- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book uses literary examples makes the case for understanding law and the legal system through the lens of philosophical pragmatism. For pragmatists, experience is everything; and they argue against understanding the world through any abstraction, maintaining that it is simply too complicated to fit into categories or theories. Legal pragmatism is the application of this philosophy to the making of law, the practice of law, and the practice of judging. This book maintains that the best way to understand legal pragmatism is not through bare theoretical exegesis but through literature; that is, through stories that cast light on various pragmatic aspects of law. Engaging a range of literary sources, including works by Seamus Heaney, Hilary Mantel, Harper Lee and Ian McEwan, the book makes a compelling case for the contemporary relevance of pragmatism. This book will appeal to legal theorists, law and literature/humanities scholars; readers of literary criticism; and those with interests in pragmatist philosophy"--
Classical pragmatism -- Pragmatism and law -- Henry James and the literary illumination of pragmatism -- The hollowness of principle and the timeless need for pragmatic compromise-Heaney's philoctetes and antigone -- Mantel's Cromwell, Harper Lee's Finch, and understanding the pragmatist as lawyer -- Crises of confidence, and understanding the pragmatic reality of judging -- The truth, the whole truth, and the legal truth -- Conclusion : waking up to pragmatism and the power of legal narrative.
Keywords: Law -- Philosophy; Pragmatism; LAW / Jurisprudence; PHILOSOPHY / Movements / Pragmatism